(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Gaining the independence by Uzbekistan enabled to restore historical justice, the names of our great ancestors and their rich heritage. Sahibkiran Amir Temur - a symbol of bravery, courage and wisdom, the Uzbek people’s national pride toke a special place in it.